Letter to Jane Tolmach from Phillip Burton - Phillip Burton:::::: (1960)
A letter from Congressman Phillip Burton that congratulates Jane Tolmach on her election as Southern Women's Chairman of the Democratic State Central Committee. He offers his assistance in helping to build the Democratic Party in California.